2020
DOI: 10.2196/preprints.21875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Telemedicine Usage Among Urologists During the COVID-19 Pandemic: Cross-Sectional Study (Preprint)

Abstract: BACKGROUND Prior to the coronavirus disease 2019 (COVID-19) pandemic, urology was one of the specialties with the lowest rates of telemedicine and videoconferencing use. Common barriers to the implementation of telemedicine included a lack of technological literacy, concerns with reimbursement, and resistance to changes in the workplace. In response to the COVID-19 pandemic declared in March 2020, the delivery of urological services globally has quickly shifted to telemedicine to accoun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…It has yet to gain widespread acceptance in the urological community because of various restrictions including patient and physician acceptability, licensure and responsibility, costs, safety, and concerns with ethical issues. A systematic review of the global challenges to telemedicine adoption found that technologyspecific concerns were the major barriers to telemedicine usage, with technically challenged employees being the most commonly identified impediment (77).…”
Section: Barriers To Telemedicinementioning
confidence: 99%
“…It has yet to gain widespread acceptance in the urological community because of various restrictions including patient and physician acceptability, licensure and responsibility, costs, safety, and concerns with ethical issues. A systematic review of the global challenges to telemedicine adoption found that technologyspecific concerns were the major barriers to telemedicine usage, with technically challenged employees being the most commonly identified impediment (77).…”
Section: Barriers To Telemedicinementioning
confidence: 99%
“…[7] The results of this study have already been widely cited in the general telehealth literature and corroborated by evidence and position statements in the specialty-speci c telehealth literature as well. [10][11][12][13][14][15] The wide variation in telehealth use across medical specialties is intriguing, since the US lacks a nationwide standardized set of telehealth reimbursement policies, which in turn, has historically posed a barrier to telehealth adoption in all specialties. [16] Despite these macro (policy-level) constraints experienced by all medical specialties, some specialties have been able to normalize telehealth to mainstream practice (e.g., Psychiatry, Cardiology); while others are just getting started during the COVID-19 pandemic (e.g., Allergy-Immunology), despite potential for all stakeholders within the specialty (e.g., patients, providers) to bene t from telehealth adoption.…”
Section: Introductionmentioning
confidence: 99%